(3Yde faS GddZI ef efXhQ eYQaj (B/s - (3GdMeOGfj, ehabs ((3YeGf, GdCQOf (B:s (3OGQ GdeSjQI hGdJhRjY hGdWHGYI,s, 2007)
(3GddZI hGdEfSGf(B.s
(3jTJed Ydi cTGa(B.s
(3HHdjhLQGajI (B: (3U(B. 267-287.s
Keywords: (3Yde GdfaS GddZhjs